2018
DOI: 10.1111/sode.12294
|View full text |Cite
|
Sign up to set email alerts
|

The participant roles of bullying in different grades: Prevalence and social status profiles

Abstract: This study examined grade differences in the social status profiles and prevalence of bullying participant roles. Participants were 598 primary school students (grades 4–6), 545 students in the lower‐grades of secondary school (grades 7–8), and 1491 students in the upper‐grades of secondary school (grades 9–11). Students' participant roles, popularity, and social preference were measured with peer nominations. Bullies, assistants, and reinforcers (i.e., bullies/followers) were as popular as defenders in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 36 publications
3
51
1
1
Order By: Relevance
“…1). In this study, the bullying and follower roles were indeed more common in adolescence than in childhood (Pouwels, van Noorden, et al, 2018).…”
Section: Prevalence Of the Participant Roles In Adolescencesupporting
confidence: 51%
See 3 more Smart Citations
“…1). In this study, the bullying and follower roles were indeed more common in adolescence than in childhood (Pouwels, van Noorden, et al, 2018).…”
Section: Prevalence Of the Participant Roles In Adolescencesupporting
confidence: 51%
“…Thornberg (2015) also found that most adolescents indicate that youths bully because they want to obtain status and power in the peer group. Thus, several studies support the idea that priority of popularity seems to drive bullying behavior in adolescence, making it a possible explanation for why bullying and following are more prevalent in adolescence than in childhood (Pouwels, van Noorden, et al, 2018), as youths prioritize popularity more strongly in adolescence than childhood (LaFontana & Cillessen, 2010). It is important to mention that the current bullying literature cannot directly confirm this idea, as developmental changes in the prevalence of bully/follower roles have not yet been associated directly with developmental changes in the underlying motivation for bullying, such as the prioritization of popularity.…”
Section: Prevalence Of the Participant Roles In Adolescencementioning
confidence: 83%
See 2 more Smart Citations
“…It is also assumed that the role of the bully more often comes to prominence in adolescence because of the wish to be popular. Meanwhile, prevalence of the role of the victim may be decreasing with age, which is related to acquisition of social skills (Pouwels et al, 2018).…”
Section: Introductionmentioning
confidence: 99%